Sàng lọc mảnh liên kết với ion kẽm trong nghiên cứu pháp triển thuốc mới ức chế glutaminyl cyclase hướng điều trị bệnh Anzheimer / Trần Phương Thảo, Hoàng Văn Hải, Trần Thị Thu Hiền - Trần, Phương Thảo
As the zinc ion is a cofactor of enzyme glutaminyl cyclase playing an important role in the catalytic action of the enzyme, and on the otherhand, all ofglutaminyl cyclase inhibitors have been designed from fragments that bind to zinc ion, but so far, the only'imidazole, benzimidazole, and phenol have been used as zinc-binding fragments ofglutaminyl cyclase inhibitors, to ﬁnd Wt "9W zinc-binding Groups of glutaminyl cyclase inhibitors, in this study 32 zinc-binding fragments were selected, synthesized and estimated the glutaminyl cyclase inhibitory activity. Of these, two fragments (2b, 7b) showed good IC50 values and ligand eﬁiciency and as such, promising for design and development of novel QC inhibitors.